2005
DOI: 10.1128/jcm.43.2.919-922.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ecoepidemiology of Laribacter hongkongensis , a Novel Bacterium Associated with Gastroenteritis

Abstract: In a territory-wide surveillance study, Laribacter hongkongensis was isolated solely from freshwater fish (60% of grass carps, 53% of bighead carps, and 25% of mud carps). Comparing the pulsed-field gel electrophoresis patterns of fish and patient isolates revealed that most patient isolates were clustered together, suggesting that some clones could be more virulent.Laribacter hongkongensis was first discovered in Hong Kong from the blood and empyema pus of a 54-year-old Chinese man with alcoholic cirrhosis (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 5 publications
2
48
0
Order By: Relevance
“…In a prospective study using cefoperazone/MacConkey agar as the selective medium (Lau et al 2003), we confirmed that L. hongkongensis is associated with communityacquired gastroenteritis and traveller's diarrhea (Woo et al 2004). Freshwater fish was confirmed to be a reservoir of it (Woo et al 2004;Teng et al 2005;Lau et al 2007). Pulsed-field gel electrophoresis (PFGE) of fish and patient isolates showed that most patient isolates were clustered together, suggesting that some clones could be more virulent than others (Teng et al 2005).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In a prospective study using cefoperazone/MacConkey agar as the selective medium (Lau et al 2003), we confirmed that L. hongkongensis is associated with communityacquired gastroenteritis and traveller's diarrhea (Woo et al 2004). Freshwater fish was confirmed to be a reservoir of it (Woo et al 2004;Teng et al 2005;Lau et al 2007). Pulsed-field gel electrophoresis (PFGE) of fish and patient isolates showed that most patient isolates were clustered together, suggesting that some clones could be more virulent than others (Teng et al 2005).…”
Section: Introductionmentioning
confidence: 53%
“…Freshwater fish was confirmed to be a reservoir of it (Woo et al 2004;Teng et al 2005;Lau et al 2007). Pulsed-field gel electrophoresis (PFGE) of fish and patient isolates showed that most patient isolates were clustered together, suggesting that some clones could be more virulent than others (Teng et al 2005). Isolation of L. hongkongensis from patients in or have recently travelled to Asia, Europe, America, and Africa implied that the bacterium is probably of global importance (Woo et al , 2005a.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the easy access to clinical specimens, the oral cavity and the gastrointestinal tract are the most important sources for bacterial discovery in humans Woo, Tse, Lau, et al, 2005;Woo, Wong, et al, 2010;Woo et al, 2014;Yuen et al, 2001). The use of 16S rRNA gene sequencing for detection has also facilitated downstream studies of these novel bacteria to help understand their disease associations, pathogenicity, transmission routes and potential reservoir(s) (Couturier, Slechta, Goulston, Fisher, & Hanson, 2012;Curreem et al, 2011;Elsendoorn, Robert, Culos, Roblot, & Burucoa, 2011;Faibis et al, 2008;Kim et al, 2011;Lau, Fan, et al, 2012Lau et al, 2005Lau et al, , 2009Lau, McNabb, et al, 2007;Lau, Wong, Li, Woo, & Yuen, 2008;Lau, Woo, Fan, Lee, et al, 2007;Lau, Woo, Fan, Ma, et al, 2007;Lau, Woo, Hui, et al, 2003;Ni et al, 2007;Smith, Pandey, & Ussher, 2012;Tang et al, 2013;Teng, Huang, et al, 2014;Teng et al, 2005;Uckay et al, 2007;Woo, Kuhnert, et al, 2003;Woo, Lau, Teng, & Yuen, 2005;Woo, Ma, et al, 2005Woo, Tam, et al, 2002;Woo, Teng, Lau, & Yuen, 2006;Woo, Teng, et al, 2004Woo, Wong, et al, 2010;Woo et al, 2014;Xiong et al, 2014;Yuen et al, 2001).…”
Section: S Rrna Gene Sequencing For Bacterial Discoverymentioning
confidence: 99%
“…L. hongkongensis is a recently discovered β-Proteobacterium that is associated with community-acquired gasteroenteritis and traveler's diarrhea (Yuen et al, 2001;Woo et al, 2004;Woo et al, 2005). It can inhabit in the intestines of freshwater fish, frogs and humans, and can also grow independently in freshwater environments (Woo et al, 2004;Teng et al, 2005;Lau et al, 2007;Ni et al, 2007;Lau et al, 2009). Therefore it needs to cope with varying environmental temperatures in these different growth habitats.…”
Section: Differential Proteomicsmentioning
confidence: 99%